Significados da prática do turismo para portadores de esclerose múltipla em seu tempo de lazer - Santini, Heloisa (My University, 2014)
The purposes of this paper were to investigate the meanings of practices of tourism for people with Multiple Sclerosis (MS) in their leisure time, revealing the real conditions of them as in the effective practice of leisure facing the possibilities and limits of the subject. That way, it was done a theory review and the essay was divided in chapters that deal with the dialectic of the body in the modern times and the leisure itself, the social reality of the MS people, and the meanings of leisure for those people. It was done a preliminary exploratory study of the theme and, from a sample by type; the investigatory process has enclosed reflexive and critical movements. The categories of analyzes: leisure, tourism and quality were remeant from the proposed referential, rebuilding the living reality of the people with MS by a study of behavior in their time of leisure. The paper has revealed that practices of leisure and tourism have meant pleasure activities and conditions of normality to be and to be in the world.
Os objetivos deste estudo foram investigar os significados das práticas do turismo por sujeitos portadores de esclerose múltipla (EM) em seu tempo de lazer, desvelando as reais condições desses portadores de EM, quanto à efetiva prática de lazer diante das possibilidades e limites desse sujeito. Nesse sentido, foi realizada uma revisão teórica e a dissertação foi dividida em capítulos que tratam da dialética do corpo na modernidade e o lazer, a realidade social dos sujeitos portadores de EM, os significados do lazer para sujeitos portadores de EM. Foi realizado um estudo preliminar exploratório ao tema e, a partir de uma amostra por tipicidade, o processo investigatório compreendeu movimentos reflexivos e críticos. As categorias de análise: lazer, turismo e qualidade de vida foram ressignificadas a partir do referencial proposto, reconstruindo a realidade vivenciada pelos sujeitos portadores de EM, por meio de estudo do comportamento manifesto em seu tempo de lazer. O estudo revelou que as práticas de lazer e de turismo significaram atividades prazerosas e condição de normalidade para ser e estar-no-mundo.
Keywords: Turismo; Processos turísticos; Lazer; Portadores de esclerose múltipla; Tourism; Touristic processes; Leisure; Multiple sclerosis carriers